The Psychological Elements of Mehmet Nuzhet’s Written Creation - Tair Kirimov (Крымское историческое обозрение)
The article deals with life and literary heritage of the prominent figure of the Crimean Tatar literature of the pre-war period, Memet Nuzhet. Particular attention is paid to his personal qualities, the depths of his philosophical thinking, his memories. The author’s methods and ways of psychological influence on the subconscious of readers are revealed. The future man of letters was born in 1888 in the village of Haydargazi in the vicinity of the Crimean city of Kezlev (Evpatoria). His first poems were published in 1912 in “Terdzhiman” (“ Translator”) newspaper edited by Ismail Gasprinski. It is generally accepted that the most fruitful period of his creative activity dates back to the 1920 s. His works, published during the very short period of national independence of the Crimean Tatars People’s Republic and under the Soviet regime in such journals and magazines as “Millet” (“Nation”), “Yeni Dunia” (“New World”), “İleri” (“Move on”, “Kozaydin” (“Glad tidings”), were signed with pseudonyms of Tuyrevich and Chelebizade Haydargazi. In 1928–1930s, by the order of the Central Committee about New Crimean Alphabet, he translated the works of renowned Russian writers into Crimean Tatar language and published them in separate books. In the last years of his life he worked as a teacher in a rural school. Then, because of his class position, the writer was persecuted by the communist authorities. Being in a state of constant stress, he fell seriously ill, got to the hospital, where died on May 4, 1934.